Phylogenetic relationships in Origanum spp. based on rDNA sequences and intra-genetic variation of Greek O. vulgare subsp. hirtum revealed by RAPD - Katsiotis, Andreas; Nikoloudakis, Nikolaos; Linos, Athanasios A.; Drossou, Anna; Constantinidis, Theophanis H. (My University, 2009)
Origanum species are among the most widely spread herbs in the Mediterranean basin. Eventhough they are used as a spice, evaluation of their genetic diversity and evolution has only recently drawn attention. In order to study phylogenetic relationships, 14 ITS1-5.8S-ITS2 clones belonging to the most common Origanum species were sequenced and a parsimony tree was constructed, using the approximate likelihood ratio test. All Origanum species were clearly separated from allied genera of the Mentheae tribe while a clear distinction between the Greek and the Spanish accessions was revealed. In addition the germplasm variability of the most common Greek oregano (O. vulgare subsp. hirtum) was investigated using the RAPD markers. The use of 10 random decamers resulted in 133 unambiguous and reproducible bands detected across 27 entries. Two main groups were identified by the UPGMA clustering using Jaccard's similarity coefficient, and major genetic dissimilarities among Greek O. vulgare subsp. hirtum populations and O. onites/O. virens species were detected. Analysis of molecular variance revealed that genetic variability is distributed mainly within populations; however, significant Φst values were detected between different geographical localities, supporting noteworthy genetic differentiation among O. vulgare subsp. hirtum populations. © 2009 Elsevier B.V. All rights reserved.
Keywords: Intra-genetic variability; ITS; Origanum; Phylogenetic relationships; RAPD